Combustion characteristics and performance of a Wankel engine for unmanned aerial vehicles at various altitudes - Kucuk, Merve; Sürmen, Ali; Şener, Ramazan (Elsevier Ltd, 2024)
This study investigates the effects of altitude on the combustion, emissions, and performance of a Wankel engine for unmanned aerial vehicles (UAVs). The main motivation behind the presented study is to contribute to the Wankel engine designs used as a power source in UAVs by revealing the operating conditions at various altitudes. For these purposes, a gasoline fueled Wankel engine was simulated at sea level conditions for different equivalence ratios and results were validated with their experimental counterparts. Then, CFD simulations were carried out at various altitudes (6000 ft, 10,000 ft, and 15,000 ft). The simulation results show that decreasing ambient air temperature, and pressure at higher altitudes reduces the fresh charge density, hence combustion efficiency and heat release rate (HRR). As a result, the performance characteristics such as the indicated mean effective pressure (IMEP), the indicated torque, and indicated power decrease and exhaust emissions increase. For 6000 rpm, IMEP decreases by 39.11%, 53.79%, and 69.22%, and the indicated power reduces by 35.51%, 52.47%, and 65.05% at the altitudes of 6000 ft, 10,000 ft, and 15,000 ft, respectively, compared to those obtained at the sea level conditions. As for exhaust emissions, CO and CO2 are lowest at sea level conditions and increase with altitude. © 2023 Elsevier Ltd
Keywords: CFD; Combustion; Emission; High altitude; UAV; Wankel engine